2014
DOI: 10.11607/jomi.3806
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast Response to Titanium Surfaces Coated with Strontium Ranelate–Loaded Chitosan Film

Abstract: These results indicated that SR-loaded chitosan film on a titanium surface promotes osteoblast proliferation and differentiation in a dose-dependent manner, which may represent a new approach in the treatment of a titanium implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 0 publications
0
29
1
Order By: Relevance
“…Our gene expression data showed SrHAn double activity on OBs and OCs. Several studies reported that strontium modulates alkaline phosphatase (ALP) activity and Runx-2 expression (Tian et al, 2014) in OBs and OBs progenitors while promoting Wnt/β-catenin pathway in human bone marrow derived mesenchymal stem cells (MSCs), thereby enhancing ECM secretion and osteogenic differentiation (Yang et al, 2011). Interestingly, in our study no significant variation was detected in Runx2 levels.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Our gene expression data showed SrHAn double activity on OBs and OCs. Several studies reported that strontium modulates alkaline phosphatase (ALP) activity and Runx-2 expression (Tian et al, 2014) in OBs and OBs progenitors while promoting Wnt/β-catenin pathway in human bone marrow derived mesenchymal stem cells (MSCs), thereby enhancing ECM secretion and osteogenic differentiation (Yang et al, 2011). Interestingly, in our study no significant variation was detected in Runx2 levels.…”
Section: Discussioncontrasting
confidence: 51%
“…Compelling experimental results showed the efficacy of strontium cations, as osteoinductive and anti-osteoporotic agents (Rohnke et al, 2016;Carmo et al, 2018;Li et al, 2018). Strontium modulates bone remodeling by enhancing bone formation and suppressing bone resorption (Chattopadhyay et al, 2006;Takaoka et al, 2010;Yang et al, 2011;Saidak and Marie, 2012;Tian et al, 2014) although, to date, the molecular and cellular mechanisms of strontium activity remain partially elusive. Physical-chemical properties of strontium-substituted hydroxyapatite nanoparticles in combination with calcium hydroxyapatite nanoparticles and their in vitro osteoinductivity were assessed in our previous works (Frasnelli et al, 2016;Visai et al, 2017;Cristofaro et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Locally application drug could accelerate this procedure to reach the sufficient osseointegration earlier, which is more time saving and effective than osteoporosis treatment. Tian and Nair uploaded SrR on some biomaterial to achieve the local delivery of SrR, and all got a good result of bone regeneration26,27. Nevertheless, questions about the effectiveness and safety of SrR local delivery have been raised.…”
Section: Introductionmentioning
confidence: 99%
“…Topical application of SR is a potential way to minimize these effects (49). Prostheses coated with SR may be able to inhibit aseptic loosening (50,51).…”
Section: Discussionmentioning
confidence: 99%